The Effectiveness of Reflective Parenting on Meta-Parenting and Time Perspective among Mothers of Children Aged 7 to 12 Years with Generalized Anxiety Symptoms in Isfahan - Rahimi , Shadan; Haji Heydari, Mahnaz (Applied Family Therapy Journal (AFTJ), 2025)
Objective: Generalized anxiety in children can affect the mental health and emotional functioning of parents, particularly mothers. One effective approach in this domain is reflective parenting, which contributes to improving parent–child interactions. Accordingly, the present study was conducted in 2025 in the city of Isfahan. Methods and Materials: This study employed a quasi-experimental design with a pretest–posttest control group. The statistical population consisted of all mothers of 7- to 12-year-old children with symptoms of generalized anxiety residing in Isfahan in 2025. From this population, 30 mothers were selected using purposive sampling and were randomly assigned to experimental and control groups. Participants in the experimental group received the reflective parenting program in ten 60-minute sessions, whereas participants in the control group did not receive this intervention. Research instruments included the standardized Meta-Parenting Questionnaire developed by Hawk and Holden (2006) and the Zimbardo Time Perspective Inventory (1999). The collected data were analyzed using multivariate analysis of covariance (MANCOVA) in SPSS version 27. Findings: The findings indicated that the reflective parenting program had a significant effect on the total meta-parenting score and the problem-solving subscale (p < .05). Furthermore, the program led to a significant improvement in the future subscale (p < .05). However, there were no significant differences between the experimental and control groups with respect to the appraisal, reflection, and anticipation subscales, the total time perspective score, and the negative past, positive past, present-hedonistic, and present-fatalistic subscales (p > .05). Conclusion: Therefore, it can be inferred that the reflective parenting program may be used as an effective approach to enhance meta-parenting among mothers of children with generalized anxiety symptoms and to modify their future-oriented time perspective.